A standardized extract of Echinacea purpurea containing higher chicoric acid content enhances immune function in murine macrophages and cyclophosphamide-induced immunosuppression mice - Heggar Venkataramana Sudeep; Kuluvar Gouthamchandra; Illuri Ramanaiah; Amritha Raj; Puttaswamy Naveen; Kodimule Shyamprasad (Taylor & Francis Group, 2023)
AbstractContext Preparations of Echinacea have been used by herbalists to boost the immune system.Objective In this study, Echinacea purpurea (L.) Moench (Asteraceae) extract with enriched chicoric acid content was investigated for immunomodulation.Materials and methods The standardized hydroalcoholic extract (4% chicoric acid) was prepared from the aerial parts of E. purpurea (SEP). The extract was screened for in vitro antioxidant activities, and immunomodulation in RAW 264.7 cells, at 200 and 400 µg/mL. Further, the male BALB/c mice (20-25 g) were divided into 4 groups (n = 6 per group). All the groups except control, were intraperitoneally injected with 70 mg/kg/day of cyclophosphamide (CTX) for 4 consecutive days. The treatment groups received SEP extract (100 and 200 mg/kg body weight) p.o. from day 5 to 14.Results The SEP extract inhibited DPPH (IC50 = 106.7 µg/mL), ABTS+ (IC50 = 19.88 µg/mL) and nitric oxide (IC50 = 120.1 µg/mL). The SEP extract's ORAC (oxygen radical absorbance capacity) value was 1931.63 µM TE/g. In RAW 264.7 cells, SEP extract increased the nitric oxide production by 30.76- and 39.07-fold at 200 and 400 µg/mL, respectively, compared to the untreated cells. SEP extract significantly increased phagocytosis and cytokine release (TNF-α, IL-6, and IL-1β) in the cells. Further, the extract improved immune organ indices, lymphocyte proliferation and serum cytokine levels in CTX-induced mice. The extract at 200 mg/kg significantly increased the natural killer cell activity (24.6%) and phagocytic index (28.03%) of CTX mice.Conclusion Our results strongly support SEP extract with 4% chicoric acid as a functional ingredient for immunomodulation.